Redescription of Clubiona blesti Forster, 1979 (Araneae: Clubionidae) with a preliminary molecular phylogeny of New Zealand Clubiona - Malumbres-Olarte, Jagoba; Vink, Cor J. (Zootaxa, 2012)
The New Zealand spider Clubiona blesti Forster, 1979 is redescribed, with the male described for the first time, and a pre-liminary molecular phylogenetic analysis of cytochrome c oxidase subunit I (COI) mtDNA sequences for eight species ofNew Zealand Clubiona and an outgroup from Tasmania is presented.There is considerable intraspecific variation in C. blesti, both genetic and in the morphology of copulatory organs,which may be explained by its wide distribution. The lack of a geographic structure based on consistent differences be-tween populations may suggest great dispersal ability. Given the limited sample size, further sampling and data on addi-tional genetic markers will be necessary to confirm this.The phylogenetic analysis of seven more species indicated that Clubiona cambridgei is the sister species of C. blestiand confirmed the existence of at least two monophyletic groups among the New Zealand Clubiona: species with a striped abdomen and with a spotted abdomen.